The interaction of internal and external factors in the transformation of employment patterns in Yucatán - Jimena Méndez Navarro; Susan Paulson (Eutopia: Revista de Desarrollo Economico Territorial, 2014)
Residents in rural Yucatan, Mexico, have experienced dramatic employment changes from one generation to the next: most older men are farmers, while young men work in manufacturing and services. Young women engage informal employment much more than their mothers. We examine several factors originating outside the territory, including international markets and Mexican public policies, to see how they interact with social, political and cultural processes within the territory in the development of these occupational transformations. Attention to the role gender plays in external factors as well as in territorial processes drives our analysis of a key territorial process: the implementation of national legislation for sustainable rural development.